Plume-lithosphere interaction at Santiago Island (Cape Verde) : implications for ocean island magma genesis models - Martins, Sofia Maria Marques (2015)
Tese de doutoramento, Geologia (Geoquímica), Universidade de Lisboa, Faculdade de Ciências, 2014